Cognition, ADHD Symptoms, and Functional Impairment in Children and Adolescents With Neurofibromatosis Type 1. Issue 8 (June 2021) - Payne, Jonathan M.; Haebich, Kristina M.; MacKenzie, Rachel; Walsh, Karin S.; Hearps, Stephen J. C.; Coghill, David; Barton, Belinda; Pride, Natalie A.; Ullrich, Nicole J.; Tonsgard, James H.; Viskochil, David; Schorry, Elizabeth K.; et al.
Objective: We examined the contribution of attention and executive cognitive processes to ADHD symptomatology in NF1, as well as the relationships between cognition and ADHD symptoms with functional outcomes.Methods: The study sample consisted of 141 children and adolescents with NF1. Children were administered neuropsychological tests that assessed attention and executive function, from which latent cognitive variables were derived. ADHD symptomatology, adaptive skills, and quality of life (QoL) were assessed using parent-rated questionnaires. Path analyses were conducted to test relationships among cognitive functioning, ADHD symptomatology, and functional outcomes.Results: Significant deficits were observed on all outcome variables. Cognitive variables did not predict ADHD symptomatology. Neither did they predict functional outcomes. However, elevated ADHD symptomatology significantly predicted functional outcomes.Conclusion: Irrespective of cognitive deficits, elevated ADHD symptoms in children with NF1 negatively impact daily functioning and emphasize the importance of interventions aimed at minimizing ADHD symptoms in NF1.